Analysis of The Influence of Online Consumer Reviews, Seasonal Digital Advertising and Celebrity Endorsers on Repurchase Intention of E-Commerce Consumers - Fitriyatul Bilgies, Ana; Risal Tawil, Muhamad; Mardiah, Ainil; Jusatria; Arief, Ilham (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to see whether there is an influence of advertising, celebrity endorsers, and online consumer reviews on repurchase intention. This research takes the population, namely e-commerce consumers, throughout Indonesia. The researcher used the nonprobability sampling method, which was purposive sampling. The research utilized a sample size of 100 individuals. The data gathering procedure involves the dissemination of surveys to individuals who have made purchases on many occasions and have been exposed to advertising materials. The researcher employed quantitative methodologies within an explanatory research framework in this study. This study utilizes the Statistical Product and Service Solution (SPSS) application to employ multiple linear regression analysis approaches. The research findings presented in this study are based on the application of the Multiple Linear Regression Analysis method to the collected data. The impact of advertising on the intention to repurchase is evident. The impact of celebrity endorsers on repurchase intentions is negligible. The impact of online consumer reviews on repurchase intentions is negligible. The impact of advertising, celebrity endorsements, and online consumer evaluations on repurchase intentions is significant.